1987
DOI: 10.7589/0090-3558-23.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Capture Myopathy in Wild Turkeys (Meleagris Gallopavo) Following Trapping, Handling and Transportation in Colorado

Abstract: Sixty wild turkeys were necropsied following trapping, transporting and handling during the winters of 1980-1981, 1981-1982, and 1982-1983 in order to determine the incidence of subclinical capture myopathy. Gross lesions characterized by small to large patchy, pale white streaked areas within skeletal muscle were found in 13 of 27 birds trapped with a drop net in the winter of 1982-1983. Microscopic lesions within myocardium characterized by irregular areas of coagulative necrosis, collapse of intercellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
54
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 4 publications
4
54
0
Order By: Relevance
“…Clinical signs of this condition in free-ranging birds are infrequently recorded after capture and marking operations (Spraker et al, 1987). Three of the little bustards in our study showed difficulty or inability to walk and/ or fly at the moment of release and remained near the place where they were released, until they died or were recaptured by hand.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Clinical signs of this condition in free-ranging birds are infrequently recorded after capture and marking operations (Spraker et al, 1987). Three of the little bustards in our study showed difficulty or inability to walk and/ or fly at the moment of release and remained near the place where they were released, until they died or were recaptured by hand.…”
mentioning
confidence: 64%
“…These findings suggest that the little bustard is also susceptible to capture myopathy and that the family of bustards should be considered as a risk group. Furthermore, it can increase the probability of predation (Spraker et al, 1987), and this was probably the case in two of the little bustards studied here. Since treatment is extremely difficult, caution should be exercised during capture and handling, and every effort should be made to prevent the problem.…”
mentioning
confidence: 72%
See 3 more Smart Citations